Leak bucket based admission control for content adaptation system - ZHU Jiang; SHEN Qing-guo; WANG Li (Tongxin xuebao)
Web server do content adaptation according to the characteristic parameters along with the user request.It would cost more system resource once in a heterogeneous environment where the request varied greatly.To avoid the overload of server,admission control technique must be adopted.Based on combining the terminal characteristic,seman-tic characteristic of content object and communication characteristic,user perceived Web page quality under real-time system load was evaluated and used as a reference in admission control.The leak bucket model and PID（proportional-integral-derivative） method were linked together to construct a feedback control loop.Technical analy-sis and analog simulation validate the feasible of the mechanism,and the QoS user achieved are improved in some degree.It opened up new vista of research for this research direction.